Loss of MicroRNA-21 Influences the Gut Microbiota, Causing Reduced Susceptibility in a Murine Model of Colitis. (28th March 2018) - Johnston, Daniel G W; Williams, Michelle A; Thaiss, Christoph A; Cabrera-Rubio, Raul; Raverdeau, Mathilde; McEntee, Craig; Cotter, Paul D; Elinav, Eran; O'Neill, Luke A J; Corr, Sinéad C
Abstract: Background and Aims: microRNAs regulate gene expression and influence the pathogenesis of human diseases. The present study investigated the role of microRNA-21 [miR-21] in the pathogenesis of intestinal inflammation, because miR-21 is highly expressed in inflammatory bowel disease. Inflammatory bowel disease is associated with intestinal barrier dysfunction and an altered gut microbiota. Recent studies have demonstrated that host microRNAs can shape the microbiota. Thus, we determined the influence of miR-21 on the gut microbiota and observed the subsequent impact in a dextran sodium sulphate [DSS]-induced colitis model. Methods: The influence of miR-21 on the gut microbiota and inflammation was assessed in wild-type [WT] and miR-21 –/– mice, in co-housed mice, following antibiotic depletion of the microbiota, or by colonization of germ-free [GF] mice with fecal homogenate, prior to DSS administration. We carried out 16S rRNA sequencing on WT and miR-21 –/– mice to dissect potential differences in the gut microbiota. Results: miR-21 –/– mice have reduced susceptibility to DSS-induced colitis compared with WT mice. Co-housing conferred some protection to WT mice, while GF mice colonized with fecal homogenate from miR-21 –/– were protected from DSS colitis compared with those colonized with WT homogenate. Further supporting a role for the microbiota in the observed phenotype, the protection afforded by miR-21 depletion was lost when mice were pre-treated with antibiotics. The 16S rRNA sequencing revealed significant differences in the composition of WT and miR-21 –/– intestinal microbiota. Conclusions: These findings suggest that miR-21 influences the pathogenesis of intestinal inflammation by causing propagation of a disrupted gut microbiota.